DEVELOPMENT OF MATHEMATICS LEARNING TOOLS WITH THE POWER OF TWO STRATEGY IN BUILDING SIDE SPACES FLAT - Susi Afrianti; abdurrahman (UIR PRESS, 2020)
This study aims to produce mathematics learning tools in the form of Learning Implementation Plans (RPP) and Student Worksheets (LKPD) with The Power Of Two strategy in Junior High Schools, which have been tested to be very valid. The development of learning tools in this study uses the R&D development method using the ADDIE model, namely: 1) Analyst, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The research data collection instruments were the RPP validation sheet, LKPD validation sheet, and teacher response questionnaires. The data collection technique used was validation data from 2 Lecturers of Mathematics Education FKIP UIR and two mathematics teachers at SMP Negeri 6 Siak Hulu. The technique used is validation data analysis. From the study results, the results of the RPP validation were 87.67 with a very valid category and LKPD 86.26 with a very valid category. Based on this research, it was obtained that the mathematics learning device with The Power Of Two strategy on the flat-sided geometry material in Junior High School was very valid, so the learning device could be diagnosed as a valid device to use.